Current collector, preparation method thereof and battery
By using a composite structure of a polymer layer and a metal layer in a lithium-ion battery, combining the through-hole structure and the first lithium-philic polymer material, the problems of excessive weight of current collector and uneven deposition of lithium ions are solved, and the battery is improved Energy density and cycling performance reduce the risk of dendrites and thermal runaway.
Patent Information
- Application Number
- CN202411774286.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The current collector in existing lithium-ion batteries is too heavy, resulting in low energy density and uneven deposition of lithium ions, increasing the risk of dendrite growth and affecting the safety and circulation performance of the battery.
The composite structure of the polymer layer and the metal layer is adopted to fill the first lithium-philic polymer material through the through-hole structure, combining hydrogen bonds and van der Waals forces to achieve uniform deposition of lithium ions and improve conductivity, while reducing the total weight of the current collector.
It significantly improves the energy density and thermal stability of the battery, reduces the generation of dendrites, enhances the mechanical flexibility and cycling performance of the battery, and reduces the risk of thermal runaway.
Smart Images

Figure CN119252935A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a current collector and a preparation method thereof and a battery. Background Art
[0002] Lithium-ion batteries (LIBs) have become the dominant technology for portable electronic devices, portable device power supplies, and energy storage due to their long service life and high energy efficiency. Over the past decade, the rapid development of various fields has put forward higher requirements for LIBs, especially higher energy density and better safety. In the traditional LIB structure, copper foil (ρ=8.96g / cm 3 ) or pure metal current collectors such as aluminum foil are usually used to support the active materials of the negative and positive electrodes, respectively. However, their total mass accounts for more than 15% of the total weight of the LIB, but they do not contribute to the capacity, which greatly hinders the improvement of the overall energy density of the LIB. Due to the uneven surface of the bare copper, the formed SEI film is unstable, and the lithium ion flux is usually concentrated at the tip of the bare copper, which leads to excessive local current density, uneven nucleation and growth of lithium metal, and promotes dendrite growth. Therefore, it is very necessary to induce uniform deposition of lithium from the lithium metal nucleation stage. In order to solve the problems of excessive current collector and lithium dendrites, scientific researchers have carried out a lot of research on this.
[0003] (1) Constructing a three-dimensional conductive skeleton as a host material for lithium metal can significantly improve the volume expansion problem during the lithium metal cycle. At the same time, the conductive skeleton can reduce the generation of "dead lithium" and thus improve the utilization rate of lithium metal. For example, Si-yuan Li et al. [Advanced Functional Materials 2019:1808847.] modified a layer of Co on carbon fiber. 3 O 4 Nanowires are used as lithium metal anode current collectors. The large spatial volume of the carbon fiber three-dimensional skeleton structure can buffer the volume expansion problem during the cycle. 3 O 4 The conversion reaction between lithium gives the composite current collector excellent lithium affinity. However, the three-dimensional conductive skeleton in the above literature sacrifices the structural strength of the material, resulting in a deterioration in the structural strength of the current collector.
[0004] (2) Use thinner metal current collectors, such as CN114164464A discloses a 4-8um ultra-thin lithium battery copper foil production cathode roller and cathode roller PVA process, including an O-ring and an end plate, the O-ring and the end plate are arranged at the end of the cathode roller, the O-ring is made of rubber, and the end plate is a PVC sheet. The present invention achieves a surface roughness of 0.15-0.18um on the cathode roller through the special structure of the cathode roller and the PVA method, making the copper foil crystals finer and the physical properties more excellent, while reducing the tearing and wrinkling phenomenon of the ultra-thin lithium battery copper foil in production, and improving the production efficiency of the copper foil. At the same time, the thinning of the copper foil also needs to fully consider the influence of mechanical properties, especially mechanical toughness, because the copper foil as the current collector of the negative electrode needs good mechanical toughness to relieve the stress generated by the volume change during the charging and discharging process of the active material, but the production yield and the mechanical strength of the thin foil brought about by the thinning of the foil are also limiting factors for the ultra-thin metal current collector.
[0005] (3) Promoting uniform deposition of lithium ions by constructing a lithium-philic coating or nanoarray, such as CN115911400A discloses a negative electrode current collector, a battery cell, a battery pack, a vehicle and a processing method for a negative electrode current collector, which belongs to the field of battery manufacturing technology. The negative electrode current collector includes: a copper foil having a three-dimensional cross-linked porous structure; a lithium-philic layer, the lithium-philic layer covering at least a partial area of at least one surface of the copper foil; a graphite layer, the graphite layer covering the lithium-philic layer and covering the surface of the copper foil. However, the lithium-philic coating or lithium-philic nanoarray is easy to fall off during the cycle, resulting in a decrease in the cycle performance.
[0006] Therefore, how to effectively reduce the weight of the current collector, avoid uneven lithium deposition, and improve the electrochemical performance of the battery is a technical problem that urgently needs to be solved. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a current collector and a preparation method thereof and a battery. The current collector provided by the present invention achieves the purpose of weight reduction through the coordinated cooperation of structure and material, improves the energy density of the current collector, realizes the uniform deposition of lithium, and avoids the generation of lithium dendrites; at the same time, it also plays a role in reducing the probability of thermal runaway and improving the electrochemical performance of the battery.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a current collector, the current collector comprising:
[0010] A polymer layer;
[0011] A metal layer, wherein the metal layer is located on both side surfaces of the polymer layer;
[0012] a through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector;
[0013] The holes of the through-hole structure are filled with a first lithium-philic polymer material.
[0014] The present invention achieves excellent mechanical flexibility through the coordination of the metal layer and the polymer layer structure, and the current collector is not prone to breakage. Even if it breaks, it cannot reach the standard of piercing the diaphragm, thus avoiding the occurrence of battery short circuit and reducing the probability of thermal runaway. At the same time, the density of the specific polymer and metal layer structure is much lower than that of the pure metal layer, which significantly improves the energy density of the battery. The through-hole structure cooperates with the first lithium-philic polymer material to promote the uniform deposition of lithium ions, further reduce the weight of the current collector, and compensate for the conductivity caused by the opening. Through the synergistic effect of the specific structure and material, the good conductivity of the current collector is guaranteed, the energy density and thermal stability of the battery are improved, and the uniform deposition of lithium ions is promoted, thereby improving the first efficiency and cycle performance of the battery.
[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0016] Preferably, the polymer material in the polymer layer includes any one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol, or a combination of at least two thereof.
[0017] Preferably, the weight average molecular weight of the polymer in the polymer layer is 5000-50000, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0018] Preferably, the thickness T1 of the polymer layer and the thickness T2 of the metal layer satisfy: 2 μm≤T1+T2≤6 μm.
[0019] Preferably, the thickness T1 of the polymer layer and the thickness T2 of the metal layer satisfy: 1 / 6≤T1 / T1+T2≤1 / 2.
[0020] Preferably, the thickness T1 of the polymer layer is 1-3 μm.
[0021] Preferably, the thickness T2 of the metal layer satisfies: T2 is 1-3 μm.
[0022] Preferably, the pore size of the through-hole structure is 5-20 μm.
[0023] Preferably, with the thickness direction perpendicular to the current collector as the horizontal direction, the hole center distance between adjacent through holes in the same horizontal direction is 500-5000 μm.
[0024] Preferably, the first lithium-philic polymer material includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
[0025] Preferably, the first lithiophilic polymer material is grafted with a second lithiophilic polymer material on the surface of the pores; the second lithiophilic polymer material includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
[0026] In a second aspect, the present invention provides a method for preparing the current collector as described in the first aspect, the preparation method comprising the following steps:
[0027] Compounding metal layers on both sides of the polymer layer to obtain a composite structure;
[0028] Performing pore formation along the thickness direction of the composite structure to obtain a through-hole structure penetrating the polymer layer and the metal layer;
[0029] The holes of the through-hole structure are filled with a first lithium-philic polymer material to obtain the current collector.
[0030] Preferably, the method of forming the composite metal layer comprises vacuum evaporation.
[0031] Preferably, the first lithium-philic polymer material is filled in the holes of the through-hole structure by in-situ polymerization.
[0032] Preferably, the first lithium-philic polymer material is grafted with a second lithium-philic polymer material on the surface of the pores, and the grafting method includes in-situ grafting.
[0033] Preferably, the in-situ grafting method comprises:
[0034] The first lithiophilic polymer material is used as a photoinitiator, and the monomer of the second lithiophilic polymer material is grafted with the first lithiophilic polymer material by light irradiation, so that the first lithiophilic polymer material is grafted with the second lithiophilic polymer material on the surface of the hole.
[0035] In a third aspect, the present invention further provides a battery, comprising the current collector as described in the first aspect or the current collector prepared by the preparation method as described in the second aspect.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] In the current collector provided by the present invention, the structure of the composite polymer between the two metal layers makes the current collector have excellent mechanical flexibility and is not easy to break. Even if it breaks, it cannot reach the standard of piercing the diaphragm, avoiding the occurrence of battery short circuit and reducing the probability of thermal runaway. At the same time, the structural coordination of the specific polymer and the metal layer can effectively achieve the thinning of the metal layer, so that the density of the specific composite layer structure is much lower than the density of the pure metal layer, which significantly improves the energy density of the battery. The first lithium-philic polymer material interacts with the polymer in the current collector through hydrogen bonds and van der Waals forces, thereby firmly fixing it in the through-hole structure of the current collector, which on the one hand promotes the uniform deposition of lithium ions, and on the other hand fills the holes in the through-hole structure, and also compensates for the conductivity caused by the opening. The through-hole structure ensures the connectivity of the conductivity of the front and back sides of the current collector, and further reduces the weight of the current collector. That is, the present invention ensures the good performance of the conductivity of the current collector through the synergistic effect of the specific structure and material, and improves the energy density and thermal stability of the battery, promotes the uniform deposition of lithium ions, thereby improving the first effect and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM image of the Cu-PI-Cu current collector with a through-hole structure provided in Example 1.
[0039] Figure 2 This is a SEM image of the current collector provided in Example 1. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0042] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0043] In a first specific embodiment, the present invention provides a current collector, the current collector comprising:
[0044] A polymer layer;
[0045] A metal layer, wherein the metal layer is located on both side surfaces of the polymer layer;
[0046] a through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector;
[0047] The holes of the through-hole structure are filled with a first lithium-philic polymer material.
[0048] In the current collector provided by the present invention, the structure of the composite polymer between the two metal layers makes the current collector have excellent mechanical flexibility and is not easy to break. Even if it breaks, it cannot reach the standard of piercing the diaphragm, avoiding the occurrence of battery short circuit and reducing the probability of thermal runaway. At the same time, the structural coordination of the specific polymer and the metal layer can effectively achieve the thinning of the metal layer, so that the density of the specific composite layer structure is much lower than the density of the pure metal layer, which significantly improves the energy density of the battery. The first lithium-philic polymer material interacts with the polymer in the current collector through hydrogen bonds and van der Waals forces, thereby firmly fixing it in the through-hole structure of the current collector, which on the one hand promotes the uniform deposition of lithium ions, and on the other hand fills the holes in the through-hole structure, and also compensates for the conductivity caused by the opening. The through-hole structure ensures the connectivity of the conductivity of the front and back sides of the current collector, and further reduces the weight of the current collector. That is, the present invention ensures the good performance of the conductivity of the current collector through the synergistic effect of the specific structure and material, and improves the energy density and thermal stability of the battery, promotes the uniform deposition of lithium ions, thereby improving the first effect and cycle performance of the battery.
[0049] In the current collector provided by the present invention, if the first lithium-philic polymer is not located in the through-hole structure but is located on the surface of the metal layer, good electronic conductivity cannot be achieved.
[0050] As a preferred technical solution in the first specific embodiment, the polymer material in the polymer layer includes any one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol, or a combination of at least two thereof.
[0051] Furthermore, the weight average molecular weight of the polymer in the polymer layer is 5000~50000, for example, 5000, 7500, 10000, 12500, 15000, 17500, 20000, 225000, 25000, 27500, 30000, 32500, 35000, 37500, 40000, 42500, 45000, 47500 or 50000, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] It should be noted that, in addition to the above-mentioned characteristic limitations, the polymer material in the polymer layer provided by the present invention is also applicable to other conventional types of polymer materials that can be used for battery current collector structures; and further, the weight-average molecular weight of the polymer provided by the present invention is 5000~50000, which ensures the flexibility of the polymer.
[0053] As a preferred technical solution in the first specific implementation, the thickness T1 of the polymer layer and the thickness T2 of the metal layer satisfy: 2μm≤T1+T2≤6μm, for example 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm or 6μm, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] As a preferred technical solution in the first specific implementation, the thickness T1 of the polymer layer and the thickness T2 of the metal layer satisfy: 1 / 6≤T1 / T1+T2≤1 / 2, for example 1 / 6, 2 / 6 or 3 / 6, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] As a preferred technical solution in the first specific implementation, the thickness T1 of the polymer layer is 1~3μm, for example 1μm, 1.5μm, 2μm, 2.5μm or 3μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] As a preferred technical solution in the first specific implementation, the thickness T2 of the metal layer is 1~3μm, for example 1μm, 1.5μm, 2μm, 2.5μm or 3μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In the present invention, by adjusting the thickness T1 of the polymer layer and / or the thickness T2 of the metal layer and / or the parameters between T1 and T2 to satisfy the numerical range of the relationship, it is more conducive to improving the flexibility of the current collector, ensuring the conductivity and improving the energy density of the system.
[0058] As a preferred technical solution in the first specific implementation, the pore size of the through-hole structure is 5~20μm, for example 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] As a preferred technical solution in the first specific implementation embodiment, with the horizontal direction perpendicular to the thickness direction of the collector, the center distance between adjacent through holes in the same horizontal direction is 500~5000μm, for example, 500μm, 750μm, 1000μm, 1250μm, 1500μm, 1750μm, 2000μm, 2250μm, 2500μm, 2750μm, 3000μm, 3250μm, 3500μm, 3750μm, 4000μm, 4250μm, 4500μm, 4750μm or 5000μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In the present invention, the pore size of the through-hole structure is 5-20 μm and / or the hole center distance is 500-5000 μm, which can make the current collector have excellent welding effect while ensuring uniform deposition of lithium ions, and the mechanical strength of the current collector is also high.
[0061] As a preferred technical solution in the first specific embodiment, the first lithium-philic polymer material includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
[0062] In the present invention, the first lithium-philic polymer material has good affinity with lithium ions, can induce uniform nucleation of lithium metal and inhibit the growth of lithium dendrites; and the first lithium-philic polymer material has photosensitivity, can generate surface-bound free radicals to trigger surface-initiated free radical polymerization of monomers on almost any substrate.
[0063] A further preferred solution is that the first lithium-philic polymer material is grafted with a second lithium-philic polymer material on the surface of the pores.
[0064] In the present invention, in addition to having good lithium ion affinity, the first lithium-philic polymer material can also be used as a photoinitiator to achieve graft connection with the second lithium-philic polymer material having dual functions of a nanobrush and a functional group. The second lithium-philic polymer material has a large number of lithium-philic functional groups, which play a role in inducing the uniform distribution of lithium ion nucleation sites on the surface of the collector foil, increasing the possibility of nucleation and making the ion distribution uniform; and the second lithium-philic polymer material also has a nanobrush structure, which can greatly improve the interface wettability and affinity between the electrolyte and the collector, and further improve the migration and diffusion of lithium ions.
[0065] Specifically: the second lithium-philic polymer material includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof, preferably polyacrylamide.
[0066] In addition, it should be noted that, in the present invention, the first lithiophilic polymer material and the second lithiophilic polymer material may be of the same or different types; preferably, the first lithiophilic polymer material is polydopamine, and the second lithiophilic polymer material is polyacrylamide.
[0067] It is understandable that in order to improve the electronic conductivity of the current collector, a conductive material may also be contained in the first lithium-philic polymer material. The present invention does not limit the specific type of the conductive material, and the present invention is applicable to conventional conductive materials that can be used to improve conductivity. For example, the conductive material may be conductive carbon black, carbon nanotubes, graphite, graphene or carbon fiber, etc.
[0068] In a second specific embodiment, the present invention provides a method for preparing the current collector as described in the first specific embodiment above, the preparation method comprising the following steps:
[0069] Compounding metal layers on both sides of the polymer layer to obtain a composite structure;
[0070] Performing pore formation along the thickness direction of the composite structure to obtain a through-hole structure penetrating the polymer layer and the metal layer;
[0071] The holes of the through-hole structure are filled with a first lithium-philic polymer material to obtain the current collector.
[0072] The preparation method provided by the present invention first composites the metal layers on the surfaces of both sides of the polymer layer, and then performs a pore-forming treatment, thereby avoiding that the obtained hole structure is not through, thereby obtaining a through-hole structure, which is beneficial to the subsequent filling of the first lithium-philic polymer material; thereby obtaining a current collector structure with stable structure, good mechanical properties, and excellent electrochemical properties; at the same time, the preparation method is simple to operate, does not require a complicated processing process, and is suitable for actual production and life.
[0073] As a preferred technical solution in the second specific embodiment, the method of compounding the metal layer includes a vacuum evaporation method.
[0074] The present invention does not impose any special limitation on the composite method of the metal layer, and is applicable to any method for composite the polymer layer and the metal layer; and further, the vacuum evaporation method is adopted to accurately control the target thickness of the metal layer and to ensure uniform deposition.
[0075] Specifically, the present invention provides a specific preparation process of a vacuum evaporation method:
[0076] The polymer layer is placed in a vacuum chamber of a vacuum evaporation device, a metal target is added, and vacuum evaporation of the metal layer on both sides of the polymer surface is performed.
[0077] Optionally, during the vacuum evaporation process, the vacuum degree can be 10kPa~100kPa (for example, 10kPa, 20kPa, 30kPa, 40kPa, 50kPa, 60kPa, 70kPa, 80kPa, 90kPa or 100kPa, etc.); the temperature of the vacuum evaporation can be 300℃~3000℃ (for example, 300℃, 500℃, 1000℃, 1500℃, 2000℃, 2500℃ or 3000℃, etc.); the voltage value of the vacuum evaporation can be 100V~20000V (for example, 100V, 500V, 1000V, 2500V, 5000V, 7500V, 10000V, 12500V, 15000V, 17500V or 20000V, etc.).
[0078] As a preferred technical solution in the second specific embodiment, the first lithium-philic polymer material is filled in the holes of the through-hole structure by an in-situ polymerization method.
[0079] It should be further explained that the present invention does not limit the metal elements in the metal layer, and the present invention is applicable to conventional metal elements that can be used for battery current collectors; and the metal layer can be a pure metal layer or an alloy metal layer, etc.; for example, the metal element includes but is not limited to at least one of copper, aluminum, nickel, iron (an element of stainless steel), gold or silver; technical personnel in this field can make adaptive selection and adjustment according to the type of metal element through the above-mentioned specific vacuum evaporation process.
[0080] In a further preferred technical solution, the first lithium-philic polymer material is grafted with a second lithium-philic polymer material on the surface of the pores, and the grafting method includes in-situ grafting.
[0081] Specifically, the in-situ grafting method includes:
[0082] The first lithiophilic polymer material is used as a photoinitiator, and the monomer of the second lithiophilic polymer material is grafted with the first lithiophilic polymer material by light irradiation, so that the first lithiophilic polymer material is grafted with the second lithiophilic polymer material on the surface of the hole.
[0083] In the grafting method provided by the present invention, the first lithium-philic polymer material can be directly used as an initiator material without the need to add an additional initiator; and the second lithium-philic polymer realizes an in-situ polymerization grafting reaction.
[0084] Optionally, the light source for the illumination includes a 300W xenon lamp that simulates sunlight.
[0085] Optionally, the temperature of the illumination is 100°C to 1000°C, for example, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, and the time of the illumination is 10min to 150min, for example, 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min or 150min, etc.
[0086] It should be noted that the filling method of the first lithium-philic polymer material in the pores of the present invention can be in-situ polymerization filling or non-in-situ polymerization filling. In-situ polymerization filling is preferred, which can achieve a close combination of the first lithium-philic polymer material and the pore structure, so that the first lithium-philic polymer is firmly fixed in the through-hole structure of the current collector.
[0087] Specifically, the present invention provides a method for filling a first lithium-philic polymer material into the holes of the through-hole structure, the method comprising the following steps:
[0088] The composite structure with the through-hole structure and the monomer solution of the first lithium-philic polymer material are mixed to carry out a polymerization reaction, and then the excess first lithium-philic polymer material on the surface of the composite structure is removed to achieve the filling of the holes in the through-hole structure by the first lithium-philic polymer material.
[0089] Optionally, a buffer solution may be added during the mixing process, wherein the buffer solution includes a tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) solution; the pH value of the buffer solution is 8.0-8.3, such as 8, 8.1, 8.2 or 8.3.
[0090] Optionally, during the mixing process, a conductive material solution may be added, wherein the conductive material includes conductive carbon black (SP).
[0091] In the present invention, during the process of filling the through-hole structure with the first lithium-philic polymer material, an additional conductive material is added to further improve the electronic conductivity of the current collector.
[0092] Optionally, a mass ratio of the composite structure having a through-hole structure to a monomer of the first lithium-philic polymer material is (50-300):1, for example, 50:1, 100:1, 150:1, 200:1, 250:1 or 300:1.
[0093] In the present invention, by adjusting the mass ratio of the composite structure with the through-hole structure and the monomer of the first lithium-philic polymer material, the uniform deposition of lithium ions can be better achieved.
[0094] Optionally, the polymerization reaction is carried out under illumination, and the light source of the illumination includes an ultraviolet light source, etc.; the power of the illumination is 100W~5000W, for example, 100W, 500W, 1500W, 2000W, 2500W, 3000W, 3500W, 4000W, 4500W or 5000W, etc.
[0095] Optionally, the method for removing excess first lithium-philic polymer material on the surface of the composite structure includes a scraping method, that is, a scraper can be used to scrape off excess first lithium-philic polymer material.
[0096] In one application embodiment, the present invention further provides a battery, which includes the current collector described in the first specific embodiment or the current collector prepared by the preparation method described in the second specific embodiment.
[0097] The current collector provided by the present invention can be used in an electrode plate, for example, compounded with a coating such as an electrode active material layer to obtain an electrode plate (a positive electrode plate or a negative electrode plate); it can also be directly used as an electrode plate, that is, an electrode plate without an electrode active material layer, such as a negative electrode plate directly used as a negative terminal.
[0098] The battery provided by the present invention includes a lithium ion battery, for example, a primary lithium ion battery, a secondary lithium ion battery or a negative electrode-free lithium ion battery (a negative electrode-free lithium ion battery and only a current collector in the present application, without a negative electrode active material, etc.); and in the lithium ion battery provided above, except for the current collector defined in the present invention, the remaining preparation raw materials, preparation methods and specific structures are all conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs.
[0099] Example 1
[0100] This embodiment provides a current collector, which includes:
[0101] Polymer layer, polyimide (PI) film layer;
[0102] A metal layer and a copper layer, wherein the metal layer is located on both sides of the polymer layer;
[0103] A through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector; the holes of the through-hole structure are filled with a first lithium-philic polymer material, polydopamine (PDA), and the first lithium-philic polymer material is grafted with a second lithium-philic polymer material, polyacrylamide (PAM), on the surface of the holes.
[0104] The thickness T1 of the polymer layer is 1 μm, and the thickness T2 of the metal layer is 1 μm;
[0105] In the through-hole structure, the hole diameter is 10 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 2000 μm, with the thickness direction perpendicular to the current collector as the horizontal direction.
[0106] The preparation method of the current collector is as follows:
[0107] (1) Dissolve 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) in 40 mL of N,N-dimethylacetamide (DMAc) solvent. 2 ) under protection, stirring at room temperature for 3-4 hours to obtain a polyamic acid (PAA) solution;
[0108] Then, a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution, stirred at room temperature for 5 minutes, and then spin-coated; then placed in an oven, placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat-treated at 200°C for 10 minutes, cooled to room temperature, and a 1μm thick polyimide film (PI film) was obtained. The PI was cut into corresponding sizes and ultrasonically removed in anhydrous ethanol, 1mol / L HCl solution, and deionized water for 5 minutes. Surface oil and oxide film, put the treated PI film into the cavity of a vacuum evaporator (EB-400S, Ecopia), add a sufficient amount of target material (pure copper particles), and successively plate a 0.5μm thick metal copper layer on both sides of the PI film to obtain a Cu-PI-Cu composite current collector; use an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a through-hole structure with a pore size of 10μm and a spacing of 2×2mm along the thickness direction for the Cu-PI-Cu composite current collector. The laser wavelength used is 355nm, and the spot focusing diameter is 10μm;
[0109] (2) Prepare a buffer solution of pH=8.5 with 0.001 mol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl), and repeatedly wash the Cu-PI-Cu with a through-hole structure with deionized water to remove impurities on its surface. Fix the clean Cu-PI-Cu with a through-hole structure at the bottom of an open container, pour an appropriate amount of buffer solution into the container, and then add a mixed solution of 3g / L SP and 2g / L dopamine (the mass ratio of Cu-PI-Cu with a through-hole structure to dopamine is 100:1) into the solution. Irradiate the dopamine solution with a 36-watt ultraviolet lamp. Due to the self-polymerization reaction of dopamine assisted by ultraviolet rays, the color of the solution turns dark brown; then use a scraper to scrape off the excess polydopamine on the surface to ensure that the polydopamine is all in the pores, rinse the surface with ultrapure water, and use N 2 Drying, so that the first lithium-philic polymer material polydopamine is filled in the holes of the through-hole structure;
[0110] The PDA-modified copper foil was immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, wherein the mass fraction of acrylamide monomer was 35%, and degassed for 30 minutes by continuous dry nitrogen at room temperature, and the quartz bottle was sealed; irradiated for 1 hour by a light source (300W xenon lamp simulating sunlight) below 10 cm, and the temperature was maintained at about 25°C, so that the first lithium-philic polymer material was grafted with the second lithium-philic polymer material on the surface of the hole to obtain the current collector.
[0111] Figure 1 The SEM image of the Cu-PI-Cu current collector with a through-hole structure provided in Example 1 is shown. Figure 1 It can be seen that after the pore-making process, the obtained through-hole structure is uniform, fine and well distributed.
[0112] Figure 2 The SEM image of the current collector provided in Example 1 is shown.
[0113] Example 2
[0114] This embodiment provides a current collector, the current collector comprising:
[0115] Polymer layer, polyimide (PI) film layer;
[0116] A metal layer and a copper layer, wherein the metal layer is located on both sides of the polymer layer;
[0117] A through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector; the holes of the through-hole structure are filled with a first lithium-philic polymer material, polydopamine (PDA), and the first lithium-philic polymer material is grafted with a second lithium-philic polymer material, polyacrylamide (PAM), on the surface of the holes.
[0118] The thickness T1 of the polymer layer is 2 μm, and the thickness T2 of the metal layer is 1 μm;
[0119] In the through-hole structure, the hole diameter is 20 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 2000 μm, with the thickness direction perpendicular to the current collector as the horizontal direction.
[0120] The preparation method of the current collector is as follows:
[0121] (1) Dissolve 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) in 40 mL of N,N-dimethylacetamide (DMAc) solvent. 2 ) under protection, stirring at room temperature for 3-4 hours to obtain a polyamic acid (PAA) solution;
[0122] Then, a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution, stirred at room temperature for 5 minutes, and then spin-coated; then placed in an oven, placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat-treated at 200°C for 10 minutes, cooled to room temperature, and a 2μm thick polyimide film (PI film) was obtained. The PI was cut into corresponding sizes and ultrasonically removed in anhydrous ethanol, 1mol / L HCl solution, and deionized water for 5 minutes. Remove the surface oil and oxide film, put the treated PI film into the chamber of a vacuum evaporator (EB-400S, Ecopia), add a sufficient amount of target material (pure copper particles), and successively plate a 1μm thick metal copper layer on both sides of the PI film to obtain a Cu-PI-Cu composite current collector; use an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a through-hole structure with a pore size of 20μm and a spacing of 2×2mm along the thickness direction of the Cu-PI-Cu composite current collector. The laser wavelength used is 355nm, and the spot focusing diameter is 10μm;
[0123] (2) Prepare a buffer solution of pH=8.5 with 0.002 mol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl), and repeatedly wash the Cu-PI-Cu with a through-hole structure with deionized water to remove impurities on its surface. Fix the clean Cu-PI-Cu with a through-hole structure at the bottom of an open container, pour an appropriate amount of buffer solution into the container, and then add a mixed solution of 6 g / L SP and 4 g / L dopamine (the mass ratio of Cu-PI-Cu with a through-hole structure to dopamine is 50:1) into the solution. Irradiate the dopamine solution with a 36-watt ultraviolet lamp. Due to the self-polymerization reaction of dopamine assisted by ultraviolet rays, the color of the solution turns dark brown; then use a scraper to scrape off the excess polydopamine on the surface to ensure that the polydopamine is all in the pores, rinse the surface with ultrapure water, and use N 2 Drying, so that the first lithium-philic polymer material polydopamine is filled in the holes of the through-hole structure;
[0124] The PDA-modified copper foil was immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, wherein the mass fraction of acrylamide monomer was 45%, and degassed by continuous dry nitrogen for 30 minutes at room temperature. The quartz bottle was sealed. The foil was irradiated with a light source (300W xenon lamp simulating sunlight) below 10 cm for 1 hour, and the temperature was maintained at about 25°C, so that the first lithium-philic polymer material was grafted with the second lithium-philic polymer material on the surface of the hole to obtain the current collector.
[0125] Example 3
[0126] This embodiment provides a current collector, the current collector comprising:
[0127] Polymer layer, polyimide (PI) film layer;
[0128] A metal layer and a copper layer, wherein the metal layer is located on both sides of the polymer layer;
[0129] A through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector; the holes of the through-hole structure are filled with a first lithium-philic polymer material, polydopamine (PDA), and the first lithium-philic polymer material is grafted with a second lithium-philic polymer material, polyacrylamide (PAM), on the surface of the holes.
[0130] The thickness T1 of the polymer layer is 1 μm, and the thickness T2 of the metal layer is 3 μm;
[0131] In the through-hole structure, the hole diameter is 5 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 1000 μm, with the thickness direction perpendicular to the current collector as the horizontal direction.
[0132] The preparation method of the current collector is as follows:
[0133] (1) Dissolve 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) in 40 mL of N,N-dimethylacetamide (DMAc) solvent. 2 ) under protection, stirring at room temperature for 3-4 hours to obtain a polyamic acid (PAA) solution;
[0134] Then, a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution, stirred at room temperature for 5 minutes, and then spin-coated; then placed in an oven, placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat treated at 200°C for 10 minutes, cooled to room temperature, and a 1μm thick polyimide film (PI film) was obtained. The PI was cut into corresponding sizes and ultrasonically removed in anhydrous ethanol, 1mol / L HCl solution, and deionized water for 5 minutes. Remove the surface oil and oxide film, put the treated PI film into the chamber of a vacuum evaporator (EB-400S, Ecopia), add a sufficient amount of target material (pure copper particles), and successively plate a 3μm thick metal copper layer on both sides of the PI film to obtain a Cu-PI-Cu composite current collector; use an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a through-hole structure with a pore size of 5μm and a spacing of 1×1mm along the thickness direction of the Cu-PI-Cu composite current collector. The laser wavelength used is 355nm, and the spot focusing diameter is 10μm;
[0135] (2) Prepare a buffer solution with pH=8.5 by using 0.0005 mol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl), and repeatedly wash the Cu-PI-Cu with a through-hole structure with deionized water to remove impurities on its surface. Fix the clean Cu-PI-Cu with a through-hole structure at the bottom of an open container, pour an appropriate amount of buffer solution into the container, and then add a mixed solution of 1.5 g / L SP and 1 g / L dopamine (the mass ratio of Cu-PI-Cu with a through-hole structure to dopamine is 300:1) into the solution. Irradiate the dopamine solution with a 36-watt ultraviolet lamp. Due to the self-polymerization reaction of dopamine under the assistance of ultraviolet light, the color of the solution turns dark brown; then use a scraper to scrape off the excess polydopamine on the surface to ensure that the polydopamine is all in the pores, rinse the surface with ultrapure water, and use N 2 Drying, so that the first lithium-philic polymer material polydopamine is filled in the holes of the through-hole structure;
[0136] The PDA-modified copper foil was immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, wherein the mass fraction of acrylamide monomer was 25%, and degassed by continuous dry nitrogen for 30 minutes at room temperature. The quartz bottle was sealed. The foil was irradiated with a light source (300W xenon lamp simulating sunlight) below 10 cm for 1 hour, and the temperature was maintained at about 25°C, so that the first lithium-philic polymer material was grafted with the second lithium-philic polymer material on the surface of the hole to obtain the current collector.
[0137] Example 4
[0138] This embodiment provides a current collector, which includes:
[0139] Polymer layer, polyimide (PI) film layer;
[0140] A metal layer and a copper layer, wherein the metal layer is located on both sides of the polymer layer;
[0141] A through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector; the holes of the through-hole structure are filled with a first lithium-philic polymer material, polydopamine (PDA), and the first lithium-philic polymer material is grafted with a second lithium-philic polymer material, polyacrylamide (PAM), on the surface of the holes.
[0142] The thickness T1 of the polymer layer is 2 μm, and the thickness T2 of the metal layer is 2 μm;
[0143] In the through-hole structure, the hole diameter is 20 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 1000 μm, with the thickness direction perpendicular to the current collector as the horizontal direction.
[0144] The preparation method of the current collector is as follows:
[0145] (1) Dissolve 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) in 40 mL of N,N-dimethylacetamide (DMAc) solvent. 2 ) under protection, stirring at room temperature for 3-4 hours to obtain a polyamic acid (PAA) solution;
[0146] Then, a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution, stirred at room temperature for 5 minutes, and then spin-coated; then placed in an oven, placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat-treated at 200°C for 10 minutes, cooled to room temperature, and a 2μm thick polyimide film (PI film) was obtained. The PI was cut into corresponding sizes and ultrasonically removed in anhydrous ethanol, 1mol / L HCl solution, and deionized water for 5 minutes. Remove the surface oil and oxide film, put the treated PI film into the chamber of a vacuum evaporator (EB-400S, Ecopia), add a sufficient amount of target material (pure copper particles), and successively plate a 2μm thick metal copper layer on both sides of the PI film to obtain a Cu-PI-Cu composite current collector; use an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a through-hole structure with a pore size of 20μm and a spacing of 1×1mm along the thickness direction of the Cu-PI-Cu composite current collector. The laser wavelength used is 355nm, and the spot focusing diameter is 10μm;
[0147] (2) Prepare a buffer solution with pH=8.5 by using 0.002 mol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl), and repeatedly wash the Cu-PI-Cu with a through-hole structure with deionized water to remove impurities on its surface. Fix the clean Cu-PI-Cu with a through-hole structure at the bottom of an open container, and pour an appropriate amount of buffer solution into the container. Then add a mixed solution of 3g / L SP and 2g / L dopamine to the solution, and irradiate the dopamine solution with a 36-watt ultraviolet lamp. Due to the self-polymerization reaction of dopamine under the assistance of ultraviolet light, the color of the solution turns dark brown; then use a scraper to scrape off the excess polydopamine on the surface to ensure that the polydopamine is all in the pores, rinse the surface with ultrapure water, and use N 2 Drying, so that the first lithium-philic polymer material polydopamine is filled in the holes of the through-hole structure;
[0148] The PDA-modified copper foil was immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, wherein the mass fraction of acrylamide monomer was 45%, and degassed by continuous dry nitrogen for 30 minutes at room temperature. The quartz bottle was sealed. The foil was irradiated with a light source (300W xenon lamp simulating sunlight) below 10 cm for 1 hour, and the temperature was maintained at about 25°C, so that the first lithium-philic polymer material was grafted with the second lithium-philic polymer material on the surface of the hole to obtain the current collector.
[0149] Example 5
[0150] This embodiment provides a current collector, which includes:
[0151] Polymer layer, polyimide (PI) film layer;
[0152] A metal layer and a copper layer, wherein the metal layer is located on both sides of the polymer layer;
[0153] A through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector; the holes of the through-hole structure are filled with a first lithium-philic polymer material, polydopamine (PDA), and the first lithium-philic polymer material is grafted with a second lithium-philic polymer material, polyacrylamide (PAM), on the surface of the holes.
[0154] The thickness T1 of the polymer layer is 3 μm, and the thickness T2 of the metal layer is 1 μm;
[0155] In the through-hole structure, the hole diameter is 5 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 500 μm, with the thickness direction perpendicular to the current collector as the horizontal direction.
[0156] The preparation method of the current collector is as follows:
[0157] (1) Dissolve 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) in 40 mL of N,N-dimethylacetamide (DMAc) solvent. 2 ) under protection, stirring at room temperature for 3-4 hours to obtain a polyamic acid (PAA) solution;
[0158] Then, a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution, stirred at room temperature for 5 minutes, and then spin-coated; then placed in an oven, placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat treated at 200°C for 10 minutes, cooled to room temperature, and a 3μm thick polyimide film (PI film) was obtained. The PI was cut into corresponding sizes and respectively dried in anhydrous ethanol, 1mol / L HCl solution, and deionized water. The surface oil and oxide film were removed by ultrasonic treatment in water for 5 min. The treated PI film was placed in the cavity of a vacuum evaporator (EB-400S, Ecopia), and a sufficient amount of target material (pure copper particles) was added to successively plate a 1 μm thick metal copper layer on both sides of the PI film to obtain a Cu-PI-Cu composite current collector. A through-hole structure with a pore size of 5 μm and a spacing of 0.5×0.5 mm along the thickness direction was prepared for the Cu-PI-Cu composite current collector using an ultraviolet picosecond laser drilling machine (LASER06007). Figure 1 As shown), the laser wavelength used is 355nm, and the spot focus diameter is 10μm;
[0159] (2) Prepare a buffer solution with pH=8.5 by using 0.002 mol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl), and repeatedly wash the Cu-PI-Cu with a through-hole structure with deionized water to remove impurities on its surface. Fix the clean Cu-PI-Cu with a through-hole structure at the bottom of an open container, and pour an appropriate amount of buffer solution into the container. Then add a mixed solution of 3g / L SP and 2g / L dopamine to the solution, and irradiate the dopamine solution with a 36-watt ultraviolet lamp. Due to the self-polymerization reaction of dopamine under the assistance of ultraviolet light, the color of the solution turns dark brown; then use a scraper to scrape off the excess polydopamine on the surface to ensure that the polydopamine is all in the pores, rinse the surface with ultrapure water, and use N 2 Drying, so that the first lithium-philic polymer material polydopamine is filled in the holes of the through-hole structure;
[0160] The PDA-modified copper foil was immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, wherein the mass fraction of acrylamide monomer was 25%, and degassed by continuous dry nitrogen for 30 minutes at room temperature. The quartz bottle was sealed. The foil was irradiated with a light source (300W xenon lamp simulating sunlight) below 10 cm for 1 hour, and the temperature was maintained at about 25°C, so that the first lithium-philic polymer material was grafted with the second lithium-philic polymer material on the surface of the hole to obtain the current collector.
[0161] Example 6
[0162] The difference between this embodiment and embodiment 1 is that the polymer in the polymer layer of this embodiment is polyethylene terephthalate (PET), and the first lithium-philic polymer material is polyvinyl alcohol.
[0163] In the preparation method, the PEI film is directly used for evaporation of the metal copper layer;
[0164] The monomer of the first lithiophilic polymer is vinyl alcohol.
[0165] The rest of the preparation methods and parameters were the same as those in Example 1.
[0166] Example 7
[0167] The difference between this embodiment and embodiment 1 is that in the through hole structure of this embodiment, the hole size is 3 μm.
[0168] In the preparation method, the parameters of pore formation can be adaptively adjusted.
[0169] The rest of the preparation methods and parameters were the same as those in Example 1.
[0170] Example 8
[0171] The difference between this embodiment and embodiment 1 is that in the through hole structure of this embodiment, the hole size is 25 μm.
[0172] In the preparation method, the parameters of pore formation can be adaptively adjusted.
[0173] The rest of the preparation methods and parameters were the same as those in Example 1.
[0174] Example 9
[0175] The difference between this embodiment and embodiment 1 is that the thickness T1 of the polymer layer in this embodiment is 0.5 μm.
[0176] The rest of the preparation methods and parameters were the same as those in Example 1.
[0177] Example 10
[0178] The difference between this embodiment and embodiment 1 is that the thickness T1 of the polymer layer in this embodiment is 5 μm.
[0179] The rest of the preparation methods and parameters were the same as those in Example 1.
[0180] Embodiment 11
[0181] The difference between this embodiment and embodiment 1 is that the thickness T2 of the metal layer in this embodiment is 0.5 μm.
[0182] The rest of the preparation methods and parameters were the same as those in Example 1.
[0183] Example 12
[0184] The difference between this embodiment and embodiment 1 is that the thickness T2 of the metal layer in this embodiment is 5 μm.
[0185] The rest of the preparation methods and parameters were the same as those in Example 1.
[0186] Example 13
[0187] The difference between this embodiment and embodiment 1 is that this embodiment does not contain the second lithium-philic polymer material PMA.
[0188] In the preparation method, after the first lithium-philic polymer material polydopamine is filled in the holes of the through-hole structure, the reaction is terminated.
[0189] The rest of the preparation methods and parameters were the same as those in Example 1.
[0190] Embodiment 14
[0191] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of Cu-PI-Cu with a through-hole structure to dopamine is 350:1.
[0192] The rest of the preparation methods and parameters were the same as those in Example 1.
[0193] Comparative Example 1
[0194] The difference between this comparative example and Example 1 is that the current collector provided in this comparative example has no through-hole structure and is not modified with the first lithium-philic polymer material and the second lithium-philic polymer material.
[0195] In the preparation method, after the Cu-PI-Cu composite current collector without pores is prepared, the reaction is terminated to obtain the current collector.
[0196] The rest of the preparation methods and parameters were the same as those in Example 1.
[0197] Comparative Example 2
[0198] The difference between this comparative example and Example 1 is that in the current collector provided in this comparative example, the through-hole structure is filled with the second lithium-philic polymer material and does not contain the first lithium-philic material.
[0199] In step (2) of the preparation method, the Cu-PI-Cu having a through-hole structure is immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, wherein the mass fraction of the acrylamide monomer is 35%, and degassing treatment is performed for 30 minutes by continuous dry nitrogen at room temperature, and the quartz bottle is sealed; irradiation is performed for 1 hour by a light source (300W xenon lamp simulating sunlight) below 10 cm, and the temperature is maintained at about 25° C., so that the second lithium-philic polymer material is filled in the holes of the through-hole structure, thereby obtaining the current collector.
[0200] Comparative Example 3
[0201] The difference between this comparative example and Example 1 is that the current collector provided in this comparative example does not contain a through-hole structure, and the first lithium-philic polymer material is located on the surface of the metal layer away from the polymer layer.
[0202] In the preparation method, the pore-forming process in step (1) is not performed, and the scraper treatment process in step (2) is not performed.
[0203] The rest of the preparation methods and parameters were the same as those in Example 1.
[0204] The current collectors provided in the embodiment and the comparative example in which the metal layer is a copper layer are used to prepare a negative electrode-free battery structure and perform a battery performance test.
[0205] i) Preparation of negative electrode-free battery structure:
[0206] The prepared composite current collector is used as a negative electrode-free current collector, that is, a negative electrode sheet, and the current collector size is (100 mm×55 mm).
[0207] Preparation of positive electrode sheet: NCM811 is used as the positive electrode active material, carbon black is used as the conductive agent, and PVDF is used as the binder. The positive electrode active material, the conductive agent, and the binder are mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone (NMP) is added to prepare the positive electrode slurry. The solid content is controlled to be 65%~70%. 12μm aluminum foil is used as the positive electrode current collector. The positive electrode sheet is prepared by coating and drying. The size of the positive electrode sheet is 96mm×51mm.
[0208] Celgard2320 microporous polypropylene film was used as the separator; the electrolyte was 1 mol / L LiPF 6 , dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1;
[0209] The capacity ratio of the positive electrode to the negative electrode is 1. The assembly process adopts a soft-pack lamination method. Lamination: the positive electrode sheet, the separator, and the negative electrode current collector are stacked in order to obtain a battery cell; then assembly is performed: the stacked battery cell is hot-pressed and placed in an aluminum-plastic film, and the top and side are sealed. The electrolyte is injected into the battery, and the battery after injection is sealed. The injection coefficient is 3g / Ah. The packaged battery is subjected to a formation treatment to obtain a battery to be tested.
[0210] ii) Performance Testing:
[0211] The prepared batteries of the examples and comparative examples were subjected to performance tests:
[0212] (a) Energy density: First, weigh each group of tested batteries and record the mass of the battery as m. Then, at 25°C, charge the battery at a constant current of 0.1C to 4.25V, then charge it at a constant voltage of 4.25V to a current ≤0.05C. After standing for 5 minutes, discharge it at a constant current of 0.1C to 2.8V to obtain the discharge energy Q. The battery energy density is calculated as Q / m.
[0213] (b) Initial efficiency and cycle performance: The charge and discharge cut-off voltage is 2.8-4.2 V, the charge and discharge current is 1 A / g, and the test is terminated after 2000 cycles.
[0214] (c) Thermal runaway peak temperature test method: in accordance with T / CSAE 344-2024 "Adiabatic thermal test method for thermal runaway of lithium-ion power batteries".
[0215] The test results of the above tests are shown in Table 1.
[0216] Table 1
[0217]
[0218] In summary, in the current collector provided by the present invention, the structure of the composite polymer between the two metal layers makes the current collector have excellent mechanical flexibility and is not easy to break. Even if it breaks, it cannot reach the standard of piercing the diaphragm, so that the risks in the inner section can be better avoided and the probability of thermal runaway can be reduced; at the same time, the structural coordination of the specific polymer and the metal layer can effectively achieve the thinning of the metal layer, so that the density of the specific composite layer structure is much lower than the density of the pure metal layer, which significantly improves the energy density of the battery; and the first lithium-philic polymer material interacts with the polymer in the current collector through hydrogen bonds and van der Waals forces, so as to be firmly fixed in the through-hole structure of the current collector, which on the one hand promotes the uniform deposition of lithium ions, and on the other hand fills the holes in the through-hole structure, and also compensates for the conductivity caused by the opening; and the through-hole structure ensures the connectivity of the conductivity on both sides of the current collector, and further reduces the weight of the current collector; that is, the present invention ensures the good performance of the conductivity of the current collector through the synergistic effect of the specific structure and material, and improves the energy density and thermal stability of the battery, promotes the uniform deposition of lithium ions, thereby improving the first effect and cycle performance of the battery.
[0219] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A current collector, characterized in that: The current collector comprises: polymer layer; A metal layer, wherein the metal layer is located on both side surfaces of the polymer layer; a through-hole structure, wherein the through-hole structure penetrates the polymer layer and the metal layer along the thickness direction of the current collector; The holes of the through-hole structure are filled with a first lithium-philic polymer material.
2. The current collector according to claim 1, characterized in that: The polymer layer satisfies at least one of the following conditions (a) to (b): (a) the polymer material in the polymer layer includes any one or a combination of at least two of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol; (b) The weight average molecular weight of the polymer in the polymer layer is 5,000 to 50,000.
3. The current collector according to claim 1, characterized in that: The thickness T1 of the polymer layer and the thickness T2 of the metal layer satisfy at least one of the following conditions (c) to (f): (c) 2μm≤T1+T2≤6μm; (d) 1 / 6≤T1 / T1+T2≤1 / 2; (e) T1 is 1~3μm; (f) T2 is 1~3μm.
4. The current collector according to claim 1, characterized in that: The pore size of the through-hole structure is 5-20 μm; and / or, Taking the thickness direction perpendicular to the current collector as the horizontal direction, the hole center distance between adjacent through holes in the same horizontal direction is 500-5000 μm.
5. The current collector according to claim 1, characterized in that: The first lithium-philic polymer material includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof; and / or, The first lithium-philic polymer material is grafted with a second lithium-philic polymer material on the surface of the pores; the second lithium-philic polymer material includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
6. A method for preparing a current collector according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Compounding metal layers on both sides of the polymer layer to obtain a composite structure; Performing pore formation along the thickness direction of the composite structure to obtain a through-hole structure penetrating the polymer layer and the metal layer; The holes of the through-hole structure are filled with a first lithium-philic polymer material to obtain the current collector.
7. The preparation method according to claim 6, characterized in that: The method of composite metal layer comprises vacuum evaporation method.
8. The preparation method according to claim 6, characterized in that: The first lithium-philic polymer material is filled in the holes of the through-hole structure by an in-situ polymerization method; and / or, The first lithium-philic polymer material is grafted with a second lithium-philic polymer material on the surface of the pores, and the grafting method includes in-situ grafting.
9. The preparation method according to claim 8, characterized in that: The in-situ grafting method comprises: The first lithiophilic polymer material is used as a photoinitiator, and the monomer of the second lithiophilic polymer material is grafted with the first lithiophilic polymer material by light irradiation, so that the first lithiophilic polymer material is grafted with the second lithiophilic polymer material on the surface of the hole.
10. A battery, characterized in that: The battery comprises the current collector according to any one of claims 1 to 5 or the current collector prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Current collector and preparation method and application thereof
CN113594468A
Current collector, current collector preparation method and battery comprising current collector
CN118867263A
Cited By
Composite copper foil current collector and preparation method thereof, negative electrode, lithium ion battery and electric equipment
CN120221668A
Modified lithium metal negative electrode material and preparation method thereof, composite modified lithium metal negative electrode material and preparation method thereof, and battery
CN120955087A
Composite copper foil current collector and manufacturing method therefor, negative electrode, lithium-ion battery, and electric device
WO2026199708A1
